2022
DOI: 10.1007/s00784-022-04778-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an experimental desensitizing gel on bleaching-induced tooth sensitivity after in-office bleaching—a double-blind, randomized controlled trial

Abstract: Objectives To evaluate the risk and intensity of tooth sensitivity (TS), and the efficacy of in-office bleaching after applying an experimental desensitizing gel composed of 10% calcium gluconate, 0.1% dexamethasone acetate, 10% potassium nitrate, and 5% glutaraldehyde. Material and methods In a split-mouth, double-blind, placebo-controlled study, 50 participants had their upper hemiarches randomized into experimental and placebo groups. Desensitizing and placebo gels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…In the present study, a lower risk of TS was observed (81%) compared with the clinical studies that evaluated the first version of the current in-office bleaching gel (95%-100%). 35,[41][42][43] This occurred because in the previous study, the gel was a slightly acidic with an unstable pH during the 50-min application time (starting at pH 6.5 and ending at pH 5.5). 19,28 More acidic gels tend to penetrate deeper into the pulp 29 and cause greater risk and intensity of TS.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present study, a lower risk of TS was observed (81%) compared with the clinical studies that evaluated the first version of the current in-office bleaching gel (95%-100%). 35,[41][42][43] This occurred because in the previous study, the gel was a slightly acidic with an unstable pH during the 50-min application time (starting at pH 6.5 and ending at pH 5.5). 19,28 More acidic gels tend to penetrate deeper into the pulp 29 and cause greater risk and intensity of TS.…”
Section: Discussionmentioning
confidence: 93%
“…The absolute risk and the intensity of TS were evaluated, using the Visual Analogue Scale (VAS; 0-10), being "0" = no pain and "10" = severe pain. 29,[39][40][41][42][43] The participants received a TS diary that corresponded to each dental bleaching session. In each session, the participants were instructed to record the worst result in the following times: immediately after the session of bleaching, up to 1 h after, up to 24 h after, and up to 48 h after the procedure.…”
Section: Assessment Of Tsmentioning
confidence: 99%
“…It is well-established that dental bleaching releases a significant amount of SP, a neurotransmitter that modulates pain [ 3 65 ]. In a clinical setting, this inflammatory process often manifests as intense tooth sensitivity following a bleaching procedure [ 8 9 66 ]. Initially, the pulp responds to mild stimuli by depositing reactionary dentin through the odontoblast cell layer [ 7 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, prior research has highlighted potential harmful effects associated with these procedures. These include an increase in pulp inflammation in both humans and animals, a decrease in the mineralization potential of pulp cells, and severe postoperative dental sensitivity [ 1 4 5 6 7 8 9 ]. Furthermore, patients who undergo in-office bleaching have reported a higher incidence and intensity of tooth sensitivity compared to those who opt for at-home bleaching.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Vochikovski L et al ( 2022) [15], in a split-mouth, double-blind, placebocontrolled study consisting of 50 participants, proved that a desensitizing gel composed of 10% calcium gluconate, 0.1% dexamethasone acetate, 10% potassium nitrate, and 5% glutaraldehyde applied on the teeth for 10 min before in-office bleaching does not reduce the risk and the intensity of tooth sensitivity. Ortega-Moncayo MG et al (2021) [16] evaluated the effectiveness of applying a dentifrice containing 5% potassium nitrate before and during in-office dental bleaching in reducing bleaching-induced tooth sensitivity using a test and control group.…”
Section: Discussionmentioning
confidence: 99%